Pengaruh Product Quality, Product Design, dan Celebrity Endorsment terhadap Purchase Decision Motor Matic Honda Vario 150cc di Yogyakarta - Dimas Bima Wijayanto; Muinah Fadhilah; Putri Dwi Cahyani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study is to test the Influence of Product Quality, Product Design and Celebrity Endorsement on the Purchase Decision of the Honda Vario Matic motorcycle in Yogyakarta. This research is a type of quantitative research conducted in the form of a survey of consumers who have purchased a Honda Vario 150c c automatic motorcyclein Yogyakarta. This study is to analyze the influence of variables The influence of product quality, product design and celebrity endorsement on consumer purchase decisions. To answer research questions and test the hypotheses proposed, multiple linear regression analysis tools are used. The population in this study was all consumers who had made a purchase or who were going to buy a Honda Vario motorcycle as many as 112 people with characteristics (age, gender, income of respondents, occupation ) as subjects of the study. The results showed that 1). Product Quality has a significant effect on the Purchase Decision on the Honda Vario Automatic Motorcycle in Yogyakarta City, 2). Product Design has a significant positive effect on the purchase decision on the Honda Vario Matic Motorcycle in Yogyakarta, 3). Celebrity Endorsement has a significant positive effect on the purchase decision on the Honda Vario Matic Motorcycle in Yogyakarta, 4) Product Quality, Product Design and Celebrity Endorsement influence the purchase decision on the Honda Vario automatic motorcycle in Yogyakarta. Keywords: Product Quality, Product Design, Celebrity Endorsment, Purchase Decision